Risk factors and prognosis in gestational trophoblastic neoplasia: A Review (Research, Society and Development, 2023)
Risk factors and prognosis play a crucial role in the assessment and treatment of gestational trophoblastic neoplasia (NTG), a rare and potentially serious condition that affects placental tissue during pregnancy. It is noteworthy that understanding risk factors helps healthcare professionals identify pregnant women who may be at higher risk of developing NTG. This enables earlier diagnosis and, consequently, more effective treatment. In this study, the aim was to conduct a comprehensive review of the available scientific literature to identify key risk factors associated with NTG and assess prognostic factors that influence clinical outcomes and disease progression. This research is a systematic review, emphasizing that this is a rigorous and structured approach to synthesizing available scientific evidence on a specific research topic. After analysis, the search resulted in ten scientific articles that formed the basis of the research. The information reveals that advanced gestational age, previous experience with hydatidiform mole, a history of having children, and living far from healthcare centers were identified as factors that significantly increase the risk. From this analysis of factors influencing the likelihood of developing gestational trophoblastic neoplasia and variables impacting its clinical course, we can infer that having a deep understanding of these components plays an essential role in the assessment and effective treatment of this medical condition.